2020
DOI: 10.3389/fphy.2020.00180
|View full text |Cite
|
Sign up to set email alerts
|

Is Export a Probe for Domestic Production?

Abstract: Recent works leverage export data to assess country production structure and ultimately country relative competitiveness. These works mostly rely only on the exported part of the total country output for reasons of data availability, homogeneity, and quality. Here we use the World Input-Output Database (WIOD), which offers cross-country harmonized data that accounts both for domestic production and export, to investigate to what extent export is a proxy for domestic production. We find that export mirrors rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Against this backdrop, greater structural change in production would be associated with greater economic complexity. This is more likely insofar as goods exports strongly reflect domestic production for manufacturing sectors or sectors related to physical goods (Saltarelli et al 2020).…”
Section: A Effect Of Productive Capacities On Economic Complexitymentioning
confidence: 99%
“…Against this backdrop, greater structural change in production would be associated with greater economic complexity. This is more likely insofar as goods exports strongly reflect domestic production for manufacturing sectors or sectors related to physical goods (Saltarelli et al 2020).…”
Section: A Effect Of Productive Capacities On Economic Complexitymentioning
confidence: 99%
“…While it is impossible to observe these capabilities directly, it is possible to infer the amount of complementary capabilities layered in countries and products through a bipartite network linking countries to the products they are able to export. Saltarelli et al (2020) find that countries' export patterns mirror their domestic production structures in manufacturing and sectors producing physical goods. This indicates that countries' exports serve as reasonable approximations not only of their export capabilities but also of their productive capabilities (economic complexity) in general.…”
Section: Measuring the Complexity Of Countries And Productsmentioning
confidence: 94%
“…We hypothesize that greater structural changes to production are likely to result in greater export resilience. This is because, on the one hand, Saltarelli et al (2020) have empirically demonstrated that exports of goods reflect strongly on domestic production in terms of manufacturing sectors or sectors related to physical goods; however, the link between the export of services and the production of services is less tenous. This means that greater structural changes to production are likely to be strongly associated with greater export diversification, at least for goods exports.…”
Section: Theoretical Motivationmentioning
confidence: 99%